Flip side of the pollution haven: Do export destinations matter? - Svetlana Batrakova (University College Dublin, UCD School of Economics, 2011)
This paper looks at a reverse side of the pollution haven argument by answering a question on whether environmental regulations of the destination, rather than source countries play a role. The study utilises a firm-level dataset with aggregate export destinations of Europe and rest of the world (ROW) to establish whether a firm adjusts its energy use in response to a decision to start exporting to a more (Europe) or a less (ROW) regulated destination. Although on average, no energy adjustments are found for these destinations, focusing on the most polluting industries or the most energy-intensive firms reveals that firms' decision to start exporting to Europe brings about significant energy improvements, unlike a decision to start exporting to the ROW. Further estimations suggest that no adjustments found for firms exporting to the ROW are consistent with exporting to non-OECD region.
Keywords: F18; Q56; L23; C23; 330; Export destinations; Energy; Firm level; Regulations